DEVELOPMENT OF POGIL-BASED E-WORKSHEET ON COVALENT BOND MATERIALS TO IMPROVE STUDENTS' LEARNING INDEPENDENCE - Rianajni, Arum Dwi; Ainiah, Errisya Nur; Puspita, Widia Indah; Dwiningsih, Kusumawati (JCER (Journal of Chemistry Education Research), 2024)
This research aims to create POGIL-based E-Worksheet learning media on Covalent Bond material to increase students' learning independence. This research uses R&D (Research and Development) research to produce and test the effectiveness of media by adapting the model developed by Plomp (2010). The subjects of this research were class XI students of SMAN 1 Menganti. The validity results based on assessments from experts were found to be 85.7% for content validity which was included in the very valid criteria and 90.7% for construct validity which was included in the very valid criteria. This E- Worksheet is also considered practical in terms of the student response questionnaire with a score of 77.3% or in the very practical category and the results of observations of student activities obtained a score of 88.9% or in the very practical category. Furthermore, the effectiveness results based on the learning independence questionnaire obtained an n-gain score of 0.71 or in the high category. Based on these results, this E- Worksheet can be used as a learning medium to increase students' learning independence.